2022
DOI: 10.12765/cpos-2022-16
|View full text |Cite
|
Sign up to set email alerts
|

Local Migration Regimes in Rural Areas: The Example of Refugee Reception in Saxony, Germany

Abstract: The reception of asylum seekers has challenged municipalities and their populations across Europe in recent years: Many rural villages and small and mid-sized towns had little prior experience with large numbers of asylum seekers. The housing of refugees constitutes one of the most controversial arenas and challenges for local communities within the reception process. This paper sheds light on rural case studies using the perspective of migration regimes. Local Migration Regimes constitute arenas of migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The empirical material presented above provides extensive evidence of how formal and informal arrival and migration infrastructures manifest themselves in a rural area of Greece. Similar recent research has shown that there are significant challenges and disputes in the reception and accommodation of refugees at the local and regional level (Schneider, 2022;Wehrhahn (Non-)…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The empirical material presented above provides extensive evidence of how formal and informal arrival and migration infrastructures manifest themselves in a rural area of Greece. Similar recent research has shown that there are significant challenges and disputes in the reception and accommodation of refugees at the local and regional level (Schneider, 2022;Wehrhahn (Non-)…”
Section: Discussionmentioning
confidence: 82%
“…Overall, the urban bias of migration and refugee research is also evident in the way arrival infrastructures are conceptualised and described in relation to the urban social fibre (Meeus et al, 2019;Hanhoester & Wessendorf, 2020;Wessendorf, 2021). For various reasons, many rural areas have become superdiverse and their capacity to receive, accommodate and integrate newcomers is limited due to a lack of institutional infrastructures (Wessendorf & Phillimore, 2019;Papadopoulos & Fratsea, 2021;Schneider, 2022). Furthermore, social fibre in rural areas enables informal social arrangements based on employment structure and opportunities, material wellbeing and existing social infrastructures.…”
Section: Institutional Manifestations Of Migrant Infrastructures For ...mentioning
confidence: 99%
“…This means that even when forced migrants are recognized as refugees, they have to stay three years within the bounds of the federal states or even of the municipalities that they are allocated to, if they are reliant on social welfare. Scholarship has demonstrated that the transition from accommodation centres to housing is far from smooth due to competitiveness of the already‐strained housing markets, discrimination (Adam et al, 2021) and more broadly internal/local border regimes in place (El‐Kayed & Hamann, 2018; Schneider, 2022). It also underlines the significance of networks in overcoming these disadvantages (Adam et al 2021).…”
Section: Accommodation and Housingmentioning
confidence: 99%
“…It also underlines the significance of networks in overcoming these disadvantages (Adam et al 2021). While most studies focus on the city contexts, recent literature has also spotlighted the particular hardship of the residence obligation for refugees initially assigned to rural areas as well as the potential of rural areas for integration (Mehl et al, 2023; Schneider, 2022). In this special issue, Weidinger and Kordel (2020) contributes to the literature through a long‐term empirical study combining surveys, individual, expert and household interviews in two rural areas in Bavaria.…”
Section: Accommodation and Housingmentioning
confidence: 99%